2011
DOI: 10.1016/j.jcin.2010.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of 1-Year Clinical Outcomes Using the SYNTAX Score in Patients With Acute ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: SXscore does have a role in the risk stratification of patients with STEMI having primary percutaneous coronary intervention; however, this ability can be improved through a combination with clinical variables. (Multicentre 2×2 Factorial Randomised Study Comparing Tirofiban Versus Abciximab and SES Versus BMS in AMI; NCT00229515).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(45 citation statements)
references
References 36 publications
2
39
2
2
Order By: Relevance
“…Higher SS was correlated with poor outcome, major adverse cardiovascular and cerebrovascular events in several studies [11,17]. Previous studies have shown prognostic utility of SS in patients undergoing percutaneous coronary interventions [12,18]. …”
Section: Discussionmentioning
confidence: 96%
“…Higher SS was correlated with poor outcome, major adverse cardiovascular and cerebrovascular events in several studies [11,17]. Previous studies have shown prognostic utility of SS in patients undergoing percutaneous coronary interventions [12,18]. …”
Section: Discussionmentioning
confidence: 96%
“…Severity of CAD is one of the best predictors of adverse outcome and mortality in STEMI patients [11]. In this study, the burden of atherosclerosis was evaluated by SxS.…”
Section: Discussionmentioning
confidence: 99%
“…The SxS is an anatomic scoring system and indicates the characteristics of a lesion including complexity, morphology, and location in the coronary tree. In recent studies it has been reported that high SxS is associated with clinical outcomes including mortality, mortality/reinfarction, major adverse cardiac events, any stent thrombosis at one-year follow-up and long term cardiac mortality (42 months follow-up) in patients with STEMI undergoing primary PCI [11,12]. The SxS also helps to stratify patients with multivessel and/or left main CAD to either CABG or PCI and reflects the technical difficulty of PCI [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, the small number of the reported events and the fact that this analysis did not take into account the angiographic variables associated with clinical outcomes (i.e. the Syntax score, or the residual Syntax score) did not allow us to draw safe conclusions about the additive prognostic value of CTCA in this population [149][150][151][152].…”
Section: Expert Commentarymentioning
confidence: 95%